Linkage and related analyses of Barrett's esophagus and its associated adenocarcinomas. Issue 4 (14th March 2016) - Sun, Xiangqing; Elston, Robert; Falk, Gary W.; Grady, William M.; Faulx, Ashley; Mittal, Sumeet K.; Canto, Marcia I.; Shaheen, Nicholas J.; Wang, Jean S.; Iyer, Prasad G.; Abrams, Julian A.; Willis, Joseph E.; et al.
Abstract: Background: Familial aggregation and segregation analysis studies have provided evidence of a genetic basis for esophageal adenocarcinoma (EAC) and its premalignant precursor, Barrett's esophagus (BE). We aim to demonstrate the utility of linkage analysis to identify the genomic regions that might contain the genetic variants that predispose individuals to this complex trait (BE and EAC). Methods: We genotyped 144 individuals in 42 multiplex pedigrees chosen from 1000 singly ascertained BE/EAC pedigrees, and performed both model‐based and model‐free linkage analyses, using S.A.G.E. and other software. Segregation models were fitted, from the data on both the 42 pedigrees and the 1000 pedigrees, to determine parameters for performing model‐based linkage analysis. Model‐based and model‐free linkage analyses were conducted in two sets of pedigrees: the 42 pedigrees and a subset of 18 pedigrees with female affected members that are expected to be more genetically homogeneous. Genome‐wide associations were also tested in these families. Results: Linkage analyses on the 42 pedigrees identified several regions consistently suggestive of linkage by different linkage analysis methods on chromosomes 2q31, 12q23, and 4p14. A linkage on 15q26 is the only consistent linkage region identified in the 18 female‐affected pedigrees, in which the linkage signal is higher than in the 42 pedigrees. Other tentative linkage signals are also reported. Conclusion: Our linkage study of BE/EAC pedigrees identified linkage regions on chromosomes 2, 4, 12, and 15, with some reported associations located within our linkage peaks. Our linkage results can help prioritize association tests to delineate the genetic determinants underlying susceptibility to BE and EAC. Abstract : We identified linkage regions on chromosomes 2q31, 12q23, and 15q26. Some of our linkage regions are consistent with reported genomic associations to BE and EAC. Our linkage results can help prioritize association tests to delineate the genetic determinants underlying susceptibility to Barrett's esophagus and esophageal adenocarcinomas, and help focus the search for causal genes.